KOMBINASI EKSTRAK ETANOL DAUN KEMANGI (Ocimum bacilicum L.) DAN DAUN SALAM (Syzygium polyanthum (Wight) Walp) SEBAGAI ANTIINFLAMASI PADA TIKUS (Rattus norvegicus) JANTAN YANG DIINDUKSI KARAGEN - sukmawati sukmawati; Rachmat Kosman; Nurwasi Saharuddin (As-Syifaa Jurnal Farmasi, 2018)
Inflammation is a normal protective response to tissue injury caused by physical trauma that could damage characterized by symptoms such as pain (dolor), heat (kalor), redness (rubor), swelling (tumor) and functional changes (fungsiolaesa). This research aimed to determine the anti-inflammatory effects of the ethanol extract combination of kemangi folium (Ocimum bacilicum L.) and salam folium (Syzygium polyanthum (Wight) Walp) in male rats (Rattus norvegicus) induced carrageen. This research used 15 rats divided into 5 groups: group I Na CMC (Naïve), group II Sodium Diclofenac (negative), group III was administered the ethanol extract of kemangi folium  and salam folium with dose 125:125 mg/kgBW, group IV with dose of 125:75 mg/kgBW and group V with dose 250:75 mg/kgBW. The entire of administration was done orally. The measurement of male rat foot was performed every 30 minutes to 150 minutes. The data were statistically analyzed using One Way ANOVA followed by Post Hoc LSD test. The results showed that the ethanol extract of Kemangi folium with dose of 250 mg/kgBW and the ethanol extract of Salam folium with dose of 75 mg/kgBW had the effect of decreasing the edema volume of the rat foot effectively the same as anti-inflammatory drugs NSAID where the results of statistical analysis were obtained significance (p>0.05).